Academic of environmental sciences: perception and interest in agro-ecological sector - Oliveira, Carmem Sara Pinheiro de; Lima, Allison Ferreira de (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">Agroecology is settling as a new alternative for transformation, not just in the productive point of view, but mostly about human inclusion. In this context, comes the debate about the importance of family farming as a means of sustainable production. This research aimed to evaluate the design of university students of Environmental Sciences on family agriculture and its agro-ecological perspectives. The subjects were 104 students, distributed among the courses of Biological Sciences and Ecology of the Universidade Federal do Rio Grande do Norte (UFRN), in which they were chosen at random and asked to answer a standard questionnaire with key questions on the proposed theme. The results showed that there is some knowledge about the theme addressed, however to get more interest it is necessary to promote greater learning in universities on this subject. Thus, we conclude that the understanding and performance of both courses is deficient, compromising the academic education of students who choose the professional future in this important area.